Lecturers Salary and Student Engagement in Southwestern Nigeria Universities - Timothy Olugbenga Ajadi (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2026)
Student engagement has become a recurring issue in universities across the globe. This may be due to the geometric increase in student enrolment in the universities and the desire of the universities to meet their demands on campus. As a result, this study investigated the level of student engagement and the influence of lecturer’s salary on student engagement in public universities in southwestern Nigeria. The population of the study comprised all lecturers in the seven federal government owned universities in southwest states of Nigeria with a sample size of 1,250 calculated and derived using Research Advisor’s Table at 95% degree of confidence with 5% error margin. Questionnaire was used to elicit information from respondents. The study found that, the level of students’ engagement is low and teachers’ salary has significant influence on student engagement in public universities in southwestern Nigeria. It was recommended that students should be more engaged by lecturers, and that government should increase salary of lecturers in Nigerian Universities.